Endocrine complications of celiac disease: a case report and review of the literature. (3rd April 2019) - Walker, Marcella D.; Zylberberg, Haley M.; Green, Peter H. R.; Katz, Michael S.
ABSTRACT: Purpose : The purpose of this article is to review recent literature regarding endocrine disorders related to celiac disease (CD). Methods : We describe a case report and review existing literature on the endocrine manifestations of CD. Results : CD is an autoimmune disorder characterized by intestinal inflammation in response to gluten. CD can cause a wide range of extra-intestinal complications, including endocrine manifestations. Metabolic bone disease including osteoporosis and osteopenia, vitamin D deficiency, secondary hyperparathyroidism and less frequently osteomalacia can be seen. In CD, fracture risk is increased by 30–40%, while risk for hip fracture is approximately doubled. The risk for other endocrine disorders, particularly autoimmune endocrinopathies, is also increased in those with CD compared to the general population. Epidemiologic data indicate the risk for hypothyroidism is 3–4 times higher among those with CD, while risk of type 1 diabetes is greater than double. Risk for primary adrenal insufficiency is a striking 11-fold higher in those with versus without CD, though the absolute risk is low. Fertility is reduced in women with CD before diagnosis by 37% while male fertility in the absence of hypogonadism does not appear to be affected. Other endocrine conditions including hyperthyroidism, ovarian failure, androgen insensitivity, impaired growth and growth hormone deficiency and autoimmune polyendocrine syndromes have also been associated with CD. Conclusions : CD is associated with a wide range of endocrine manifestations.